2022
DOI: 10.1097/md.0000000000028528
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional prevalence and burden for premenstrual syndrome and premenstrual dysphoric disorder

Abstract: Introduction: Premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) are becoming common mental diseases in women impairing daily functioning. Estimation of the epidemiological burden of PMS/PMDD can serve as scientific basis for prevention and management of premenstrual disorders. Herein, we firstly provide a protocol to perform estimation on the prevalence and risk factors for PMS/PMDD in the general population globally and regionally. Methods/design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Once the symptoms become severe to the point of debilitation, it meets the criteria of premenstrual dysphoric disorder (PMDD). Approximately 20–40% of young women suffer from PMS, 2–8% from PMDD, and 85% suffer from at least one symptom of PMS during their child-bearing years [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Once the symptoms become severe to the point of debilitation, it meets the criteria of premenstrual dysphoric disorder (PMDD). Approximately 20–40% of young women suffer from PMS, 2–8% from PMDD, and 85% suffer from at least one symptom of PMS during their child-bearing years [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 Epidemiological data affirm that 90% of females of reproductive age are usually impacted by mild to acute premenstrual symptoms, among them, about 20% to 40% are affected for PMS. 5 Additionally, prevalence among university students is over 50%. 6 Indeed, an investigation found that PMS affects quality of life students, particularly components related to mental and environmental health.…”
Section: Introductionmentioning
confidence: 99%
“…This requires her to face different feelings. Many women undergo changes in their bodies or moods, such as depression or weight gain (Gao et al,2022;Zaka& Mahmood,2012). The symptoms get worse during the second half of the menstrual cycle and then fade and go away after the start of the next menstrual cycle.…”
Section: Introductionmentioning
confidence: 99%